Effect of different organics amendments on some soil physical properties in a Paddy-Berseem cropping system - YADAV, NARESH KUMAR; SHARMA, VIKAS; ARYA, VIVAK M.; CHOUDHARY, RAJ SINGH; PANOTRA, N. (Journal of Soil and Water Conservation, 2022)
Organic manure application can affect the soil physical properties. In a paddy-based cropping systems there are wide variations in the soil physical characteristics throughout the crop cycle. A field investigation (2018-19; 2019-20) was conducted with eight treatments comprising of T1-Control; T2-Farm Yard Manure (FYM) (100% N); T3-Vermicompost, VC (100% N); T4 - FYM (50% N) + VC (50% N); T5-FYM (50% N) + Poultry manure, PM (50% N); T6-FYM (50% N) + Neem cake, NC (50% N); T7-VC (50% N) + PM (50% N) and T8-VC (50% N) + NC (50% N) with three replications in a Basmati rice-berseem system. The study indicated large influence of different organic sources on bulk density and porosity in both the years after the harvest of either paddy or berseem. The conjoint application of vermicompost and poultry manure reduced BD to a greater extent and significant variations was observed for water holding capacity in different treatments.